A Comprehensive Analysis of Child Labor Practices in Brick Kilns: A Case Study of Harion Municipality, Sarlahi, Nepal - Shrestha, Laxman; Singh, Shatruhan (Chaturbhujeshwar Academic Journal, 2025)
This study explores the forcible factors leading to child labor in brick kilns, focusing on Harion Municipality, Sarlahi district. It highlights poverty and illiteracy as key drivers. Using a mixed-methods approach grounded in pragmatism, data were collected through interviews with 30 children working in three brick kilns, with parental consent. Analysis, informed by Marxist discourse, reveals that child labor is the primary income source for poor, large families, mostly children aged 10 to 14. The work, characterized by harsh conditions, results in serious health issues and a high school dropout rate of 66.7%. The study exposes exploitative piece-rate wage structures and widespread unawareness of child labor laws among children and parents. The findings underscore how poverty compels seasonal migration and school dropout, trapping children in hazardous labor cycles that benefit brick kiln owners through cheap labor. To disrupt this cycle, awareness among families and institutional efforts to provide educational opportunities are essential. Addressing these issues can help break the intergenerational cycle of labor in brick kilns.